Hubungan Kompres Bawang Merah (Allium ascalonicum L.) dengan Nyeri Payudara Bengkak Pada Ibu Nifas - yuliani, ita; Suprapti, Suprapti; Yulindawati, Asworoningrum (Jurnal Pendidikan Kesehatan (e-Journal), 2024)
Swollen breasts occur due to narrowing of the lactiferous ducts and breast milk not being released completely which causes pain and fever, usually occurring on the second or third day after delivery (Ahmad, 2020). Swollen breasts (breast engorgement) will feel hot, sore and tender to touch (Rohmah et al., 2019). Swollen breasts must be treated immediately so that they do not develop into mastitis/acute infection of the mammary glands, breast abscess and septicemia (Apriani et al., 2018). This study aims to determine the relationship between red onion (Allium ascalonicum L.) compresses and swollen breast pain in postpartum women. This research method uses a correlational study research design with an experimental approach. The sample for this study was 30 postpartum mothers who met the inclusion criteria. Using purposive sampling technique. The data collection method uses primary data on treatment administration and from the pain scale (NRS) questionnaire sheet, then the data is analyzed using the Spearman Correlation Coefficient with a confidence level of 5%. The results of this study were that all (100%) postpartum mothers received shallot compresses on their breasts for 15-30 minutes, while the results of the pre-test pain scale questionnaire (NRS) showed that almost all (78%) had a moderate pain scale and a small portion (22%) had a moderate pain scale. Severe pain after being given an onion compress for 15-30 minutes was found almost entirely (88%) on a mild pain scale and a small number (13%) with moderate pain. The results of spermane correlation coefficient statistical test analysis obtained avalue of p=0,005 <0,05 and P value < ? that H0 was rejected, meaning that there was a relationship between Shallot Compress (Allium ascalonicum L.) and Swollen Breast Pain in Postpartum Mothers. Onion compresses can affect swollen breast paint in postpartum mother or is close relationship between before and after compressing with onions and swollen breast paint in postpartum mothers. It is hoped that mothers, especially postpartum mothers, will do breast compression with red onions when swollen breasts occur on days 1 to 10 of postpartum, thereby preventing complications from swollen breasts. Keywords: Red Onions , breast pain, Swollen.